IMPLEMENTASI PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYA PENANGGULANGAN KEMISKINAN DI PEKON WONODADI KECAMATAN GADINGREJO KABUPATEN PRINGSEWU - Fernanda, Reza Agung; Sulistiowati, Rahayu; Caturiani, Susana Indriyati (Administrativa : Jurnal Birokrasi, Kebijakan dan Pelayanan Publik, 2025)
The Family Hope Program (PKH) is a social protection program that provides cash assistance to Very Poor Households (RTSM) and RTSM family members are required to carry out the terms and conditions set out. Wonodadi Pekon, Gadingrejo District, Pringsewu Regency is one of the pekons implementing the family hope program. The number of KPM in Pekon Wonodadi is the highest in Gadingrejo District. However, the phenomenon that occurred was that the facilitators were less than optimal in carrying out their responsibilities and there were two changes in the PKH facilitators. This research aims toexplain and analyze the Family Hope Program (PKH) is implemented in Pekon Wonodadi, Gadingrejo District, Pringsewu Regency. The method used is a qualitative approach with a descriptive type. The results of the research show that the implementation of PKH in Wonodadi village includes PKH social assistants as the implementer and involvement of village officials in finding residents who meet the criteria, there are P2K2 activities, and there are SOPs for implementing PKH. This is in accordance with Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program. Obstacles in its implementation, such as a lack of responsibility for companions in carrying out their duties, a lack of coordination between Pekon officials, Puskesos, and companions, as well as obstacles to routine meeting activities.